Ionic conductivity of Na3Al2P3O12 glass electrolytes role of charge compensators - Keshri, Shweta R.; Ganisetti, Sudheer; Kumar, Rajesh; Gaddam, Anuraag; Illath, Kavya; Ajithkumar, Thalasseril G.; Balaji, Sathravada; Annapurna, K.; Nasani, Narendar; Krishnan, N. M. Anoop; Allu, Amarnath R. (Inorganic Chemistry, 2021)
In glasses, a sodium ion (Na+) is a significant mobile cation that takes up a dual role, that is, as a charge compensator and also as a network modifier. As a network modifier, Na+ cations modify the structural distributions and create nonbridging oxygens. As a charge compensator, Na+ cations provide imbalanced charge for oxygen that is linked between two network-forming tetrahedra. However, the factors controlling the mobility of Na+ ions in glasses, which in turn affects the ionic conductivity, remain unclear. In the current work, using high-fidelity experiments and atomistic simulations, we demonstrate that the ionic conductivity of the Na3Al2P3O12 (Si0) glass material is dependent not only on the concentration of Na+ charge carriers but also on the number of charge-compensated oxygens within its first coordination sphere. To investigate, we chose a series of glasses formulated by the substitution of Si for P in Si0 glass based on the hypothesis that Si substitution in the presence of Na+ cations increases the number of SiOAl bonds, which enhances the role of Na as a charge compensator. The structural and conductivity properties of bulk glass materials are evaluated by molecular dynamics (MD) simulations, magic angle spinning-nuclear magnetic resonance, Raman spectroscopy, and impedance spectroscopy. We observe that the increasing number of charge-imbalanced bridging oxygens (BOs) with the substitution of Si for P in Si0 glass enhances the ionic conductivity by an order of magnitudefrom 3.7 x 10(-8) S.cm(-1) to 3.3 x 10(7) S.cm(-1) at 100 degrees C. By rigorously quantifying the channel regions in the glass structure, using MD simulations, we demonstrate that the enhanced ionic conductivity can be attributed to the increased connectivity of Na-rich channels because of the increased charge-compensated BOs around the Na atoms. Overall, this study provides new insights for designing next-generation glass-based electrolytes with superior ionic conductivity for Na-ion batteries

Investigation of Al2O3 induced variations in the structural parameters in strontium borosilicate glasses using solid state NMR - Illath, Kavya; Ojha, Prasanta K.; Rath, Sangram K.; Ajithkumar, T. G. (Physical Chemistry Chemical Physics, 2023)
The physical properties of oxide glasses are crucially dependent on the atomistic structural speciation. In this study, we investigate the variation in the local ordering in the glass network of strontium borosilicate glasses (34.82 SrO, 51.84 B2O3, 13.34 SiO2 in mol%) with a progressive substitution of B2O3 by Al2O3 and estimate the structural parameters: the oxygen packing fraction, and the average network coordination number. The coordination of the network forming cations at various glass compositions is determined using B-11, Al-27, and Si-29 solid-state nuclear magnetic resonance (SSNMR). The SSNMR reveals that at the higher substitution of B2O3 by Al2O3 in the glass composition, the coordination network of Al3+ exists predominantly in the 4 coordinated state, the network forming B3+ cations transform from a tetrahedral BO4 to a trigonal BO3 structure, and the Q(4) form of silicates is dominant. The average coordination number and the oxygen packing fraction were calculated using the parameters obtained from the SSNMR results, and it is observed that the average coordination number decreases, and the oxygen packing fraction increases on incorporating Al. It is interesting to note that some of the thermophysical properties of these compositions closely follow the pattern shown by the average coordination number and the oxygen packing fraction.

Insights into the Chemical Durability and Structure of ZnO-Incorporated Sodium Borosilicate Glasses from Solid-State NMR - Illath, Kavya; Ananthanarayanan, Arvind; Banerjee, D.; Mishra, R. K.; Kumar, Ravi; Bhattacharya, D.; Kumar, Sanjay; Manohar, S.; Ajithkumar, T. G. (Journal of Physical Chemistry B, 2025)
ZnO-incorporated NBS glasses have been studied for their application as a matrix for nuclear waste immobilization. However, structural factors affecting chemical durability have not been established. In this study, the structural changes in NBSZn glasses across various Na2O/(B2O3 + ZnO) ratios are explored using multinuclear MAS, MQMAS NMR, and EXAFS techniques. The Na MAS and MQMAS studies reveal remarkable changes in the Na environment after ZnO incorporation, which leads to an increase in chemical durability. Based on the results from NMR and EXAFS, we rationalized the structure of this glass in terms of the modified random network (MRN) model. The glass network comprises a highly polymerized region and alkali percolation channels bordered by nonbridging oxygens from the depolymerized regions. The constriction of these percolation channels increases the chemical durability of the glass. Our findings will help in the advancement of Zn-containing NBS glasses as a promising matrix for nuclear waste immobilization.